Human-Machine Creativity – How AI Can Influence Human Creativity in Open Innovation - Melanie Clegg; Reto Hofstetter; Ivo Blohm; Marc Bravin (Marketing Review St.Gallen, 2022)
Innovation platforms are powerful instruments for harnessing crowd creativity. Yet, platform users still struggle with cognitive barriers when looking to unfold their creative potential. This conceptual article identifies three barriers from innovation literature and outlines how artificial intelligence can help users overcome these barriers.
Keywords: 650